Results of direct shear experiments on intact and powdered samples from the submarine flank of Kilauea volcano (Hawaii, USA): Velocity-dependent Friction Measurements, Input Parameters for Forward Modeling - Fiene Stoepke; Matt J Ikari; Julia K Morgan; Morelia Urlaub (PANGAEA, 2025)
We performed laboratory friction experiments on simulated fault gouges and intact samples from the submarine flank of Kilauea volcano (Hawaii, USA) and measured the velocity-dependence of friction in velocity-step tests. Moreover, we have directly measured cohesion on the fault gouge and intact samples from Kilauea extquotesingles submarine flank. The experiments were carried out using a single-direct shear device at room temperature. For the shearing tests, the samples simulating fault gouge were crushed and sieved to a grain size of < 125 μm. The intact samples were tested as mini-cores. All experiments were carried out under fluid-saturated conditions (3.5 % NaCl brine) and under an effective normal load of 10 MPa.
In: Stoepke, F et al. (2025): Results of direct shear experiments on intact and powdered samples from the submarine flank of Kilauea volcano (Hawaii, USA) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.985068